POLYCYSTIC KIDNEYS - Anwar, Mohammad Shamim (Journal of Ayub Medical College Abbottabad, 1995)
Adult polycystic disease of the kidneys is not uncommon. The commonest mode of presentation is with dull abdominal pain. Hypertension is common. I report three cases of the disease to increase awareness.